External Debts, Institutions and Growth in SSA. Issue 4 (2nd October 2018) - Mensah, Lord; Bokpin, Godfred; Boachie-Yiadom, Eric
ABSTRACT: The study investigates the impact of institutional quality on the external debt–growth nexus in SSA. Data from 36 SSA economies over the 1996–2013 periods were used. The results from the IV-System GMM imply that institutional quality has robust effects on the external debt–growth nexus. Thus, the impact of external debt on growth is through host nation's institutional quality. However, the mediating effect of institutional quality on this nexus is up to a point. When a country is on the wrong side of the debt-laffer curve, external debt becomes irrelevant; and institutional quality can no longer help.